Clusters in Tourist Trade in Czech Part of the Euroregion Nisa - Kraft, Jiri; Śimanova, Jana (Klastry w ruchu turystycznym w czeskiej części Euroregionu Nysa, 2008)
The significant persumption of sufficient development of tourist trade branch in the market economy is Existance of functional partnership. Founding of cluster is long-term a financial demanding task. Except the personal costs it is necessary to count with cost of virtual environment form of communication, separate tourist trade portal which would serve not only regionl visitors but above all current and potential members of cluster. (excerpt from the conclusion)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 217-228